2020
DOI: 10.1177/1528083720935570
|View full text |Cite
|
Sign up to set email alerts
|

Performance of fiber metal laminate composites embedded with AL and CU wire mesh

Abstract: This work was investigated that the effect of aluminium (Al) and copper (Cu) wire mesh embedded as a structural reinforcement on jute epoxy hybrid composite. The hybrid composites were prepared by epoxy LY556 with HY951 hardener as a matrix; jute and wire mesh as reinforcements using the compression molding technique. In hybrid composites, the aluminium wire mesh (AWM) and copper wire mesh (CWM) were embedded as 45° & 90° orientation to the jute fiber (AWM45/90 and CWM45/90). The performance of the fabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Various studies on the hybridization of natural fiber with FML have been reported, as listed in Table 6. Woven mat jute fiber Aluminum and copper Epoxy Compression molding [185] Plain woven kenaf and woven E-glass Annealed aluminum PP Hot pressing [186] Plain and twill woven kenaf and PALF Aluminum PP Hot molding compression [187] Vieira et al [182] performed the investigation on composites of sisal fiber-reinforced aluminum laminates (SiRALs) and sisal fiber-reinforced composites (SFRC) on their physical and mechanical properties. Characterizations of the composites showed remarkable enhancements of the tensile, flexural, and impact properties (Figure 11) in SiRAL due to presence of aluminum layers in the composite system.…”
Section: Mechanical Performance Of Hybrid Natural Fiber/synthetic Fiber-reinforced Polymer Compositesmentioning
confidence: 99%
“…Various studies on the hybridization of natural fiber with FML have been reported, as listed in Table 6. Woven mat jute fiber Aluminum and copper Epoxy Compression molding [185] Plain woven kenaf and woven E-glass Annealed aluminum PP Hot pressing [186] Plain and twill woven kenaf and PALF Aluminum PP Hot molding compression [187] Vieira et al [182] performed the investigation on composites of sisal fiber-reinforced aluminum laminates (SiRALs) and sisal fiber-reinforced composites (SFRC) on their physical and mechanical properties. Characterizations of the composites showed remarkable enhancements of the tensile, flexural, and impact properties (Figure 11) in SiRAL due to presence of aluminum layers in the composite system.…”
Section: Mechanical Performance Of Hybrid Natural Fiber/synthetic Fiber-reinforced Polymer Compositesmentioning
confidence: 99%
“…The flexural test samples were prepared using the ASTM D790-17 with a dimension of 120 × 25 × 3 mm 3 [31]. The flexural specimen was subjected to a three-point bend test, and it was conducted in the universal testing machine (UTM) (Figure 3(b)) [32]. The span length between two supports was 90 mm, with a crosshead speed of 1 mm/min was preferred.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 lists the metallic fillers used in FR applications. In some polymer composites, the metal and natural fibers such as kenaf [ 65 ], flax [ 66 ], and jute [ 67 ] have been added together with the polymeric resin to enhance the structural and thermal stability. Krishnasamy et al [ 65 ] reported that the addition of aluminum and copper in jute epoxy hybrid composite resulted in the excellent thermal stability, as well as improved in their mechanical strength such as tensile and flexural performance.…”
Section: Introductionmentioning
confidence: 99%